Safety, Pharmacokinetics, and Pharmacodynamics of a Single Bolus of the γ-aminobutyric Acid (GABA) Receptor Potentiator HSK3486 in Healthy Chinese Elderly and Non-elderly - Li, Xiaojiao; Yang, Deming; Li, Qianqian; Wang, Hong; Wang, Meng; Yan, Pangke; Wu, Nan; Li, Fangqiong; Ma, Shiping; Ding, Yanhua; Liu, Jingrui; Wang, Hushan (Frontiers in Pharmacology, 2021)
Background: The present clinical trial investigated the potential influences of dosage and age on the pharmacokinetic properties and safety profile of HSK3486, and whether any adjustment in dosing regimen is necessary in elderly patients. Methods: Twenty-four elderly participants (65-73 y) were apportioned to 3 equal cohorts to receive a single IV bolus of 0.2, 0.3, and 0.4 mg/kg HSK3486, respectively. An additional control group comprised 8 non-elderly participants (21-44 y), who each received a single IV bolus dose of 0.4 mg/kg. Safety was assessed throughout the study, and the clinical effects were assessed based on modified observer’s assessment of alertness/sedation and bispectral index (BIS) monitor. Pharmacokinetic parameters were calculated. Results: The rates of drug-related adverse reactions among the elderly groups were a little higher than that of the non-elderly, and were slightly higher in the elderly receiving 0.4 mg/kg compared with the elderly given lower doses. The pharmacokinetic characteristics of 0.4 mg/kg HSK3486 in the elderly and non-elderly were comparable. The time to recovery was similar in elderly 0.3 mg/kg, elderly 0.4 mg/kg and non-elderly 0.4 mg/kg groups. In the elderly 0.2 mg/kg group, the time to loss of consciousness was a little longer, and the time to recovery was shorter, relative to the other three groups. Conclusions: Administration of 0.3 mg/kg to the elderly and 0.4 mg/kg to the non-elderly were similarly efficacious. A dose of HSK3486 of 0.3 mg/kg may be chosen for clinical use in elderly patients.